Free time in university students of the Facultad of Comercio and Administracion of Tampico - Ochoa-Hernández, Magda Lizet (Universidad Autónoma de Tamaulipas, 2012)
Knowing the time spent by university students in certain activities to identify priorities, habits, attitudes and interests in their daily lives. This is a descriptive, cross-sectional, quantitative, study which determines the activities that the university students do in their free time in the Facultad de Comercio y Administración de Tampico. The information was obtained by applying an ad hoc survey designed with a confidence level of 95% to 339 students of the degree in International Business, Administration, Computer Science and Public Accountant. Each degree has different results; however, the four profiles agree that spend most of their free time on internet, specifically in the social networks.